LITERASI DIGITAL WARGA BELAJAR DI PKBM DAYA GUNA DESA SESAP KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Kurnia, Rara; Ayub, Daeng; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Digital literacy is defined as the ability to understand and use information in various forms from a very wide variety of sources that are accessed through computer devices. The purpose of this study was to determine and analyze how high the digital literacy in PKBM Daya Guna Sesap Village, Tebing Tinggi District, Kepualuan Meranti Regency. Knowing and analyzing how much the contribution of digital literacy of learning citizens based on indicators of digital literacy variables of learning citizens in PKBM Daya Guna Sesap Village, Tebing Tinggi District, Kepulauan Meranti District. This research is a descriptive study with a quantitative approach to one variable. The population in this study amounted to 37 people throughout the study population. Sampling is done by random sampling technique, because the sampling of members of the population is done randomly without regard to strata that exist in that population. The instrument in this study was a questionnaire or questionnaire containing 47 statements about digital literacy contained from three indicators. The mean of the base class indicator is 4.60, then the mean of the cultural base indicator is PKBM 4.60, and the mean of the community base indicator is 4.42, which is classified as very high. Based on inferential statistical analysis, the digital literacy contribution of learning citizens is relatively high with a mean value of 76.93% and the remaining 23.07% is influenced by other indicators besides the indicators in this study.Key Words: Digital literacy, Learning Citizens, PKBM